Comparing Semi-Analytical and Numerical Modelling of the ICM Chemical Enrichment - Cora, Sofía Alejandra (2005)
The dependence of iron abundance on cluster temperature is subject to continuous debate. There are some evidences of decreasing abundances from ~0.7 to ~0.3 times the solar metallicity in the temperature range of ~3 — 10 keV, while a roughly constant value of ~0.3 times solar is claimed. Physical interpretation of these ambiguous observational results calls for robust theoretical models that can predict systematic trends for the enrichment of clusters of different masses.